Determination of Going Concern Opinion In Manufacturing Companies Listed on The Indonesia Stock Exchange (IDX) - Indupurnahayu; Sundarta, M. Imam; Nugroho, Agung; Maulani, Denia (Jurnal Manajemen, 2023)
The existence of the Covid 19 pandemic provides impact to companies in Indonesia, especially in the world of finance especially auditors, there are perspective new related opinion namely going concern towards evaluation performance company as audite, then objective exists study This is for analysis the most important factors influential For gift going concern opinion on IDX Manufacturing Companies from 2018 to 2021, application method with regression logistics on 280 samples with purposive sampling method, Based on results research, there is findings that KAP reputation , interaction between debt to asset ratio and debt to equity ratio, as well as interaction between profitability with size company own connection negative with gift going concern audit opinion. Temporary that is , annual audit opinion previously own connection positive with gift going concern audit opinion. However, no found significant relationship between profitability, debt to asset ratio, debt to equity ratio, and size company with going concern audit opinion, in general overall, findings study This show that KAP reputation, annual audit opinion previously, as well interaction between debt to asset ratio and debt to equity ratio, and interactions between profitability with size company can become indicator beginning for internal auditors give going concern opinion for evaluate health finance and sustainability company.